2020
DOI: 10.1136/ejhpharm-2020-002322
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of interleukin 6 in SARS-CoV-2 infection: siltuximab as a therapeutic option against COVID-19

Abstract: The aim of the study was to explore the involvement of interleukin 6 in SARS-CoV-2 infection, and to position the drug siltuximab in the management of severe forms of COVID-19. A bibliographic search was performed in Pubmed on the immune response to the disease, and in ClinicalTrials.gov on clinical trials with interleukin 6 blockers. Interleukin 6 is involved in the cytokine cascade, which originates as a consequence of an excessive immune response secondary to viral infection, aggravating lung affectation. B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 11 publications
1
29
0
2
Order By: Relevance
“…However, the researchers found that the effectiveness of a single dose was more significant due to the severity of SARS infection as well as the half-life of Siltuximab. It also suggested that before Siltuximab administration, it is essential to approve that total neutrophil and platelet count be higher than 1 × 10 9 cell/L and 75 × 10 9 /L, respectively [101]. Another study also demonstrated that Siltuximab had a significant role in the treatment of COVID-19 patients with ARDS [102].…”
Section: Siltuximabmentioning
confidence: 99%
“…However, the researchers found that the effectiveness of a single dose was more significant due to the severity of SARS infection as well as the half-life of Siltuximab. It also suggested that before Siltuximab administration, it is essential to approve that total neutrophil and platelet count be higher than 1 × 10 9 cell/L and 75 × 10 9 /L, respectively [101]. Another study also demonstrated that Siltuximab had a significant role in the treatment of COVID-19 patients with ARDS [102].…”
Section: Siltuximabmentioning
confidence: 99%
“…A specific drug has not yet been introduced to treat patients with COVID-19, and studies are ongoing. Although drugs such as tocilizumab [ [159] , [160] , [161] , [162] , [163] ], siltuximab [ 164 , 165 ], hydroxychloroquine [ 166 , 167 ], remdesivir [ 168 ], lopinavir/ritonavir [ 169 ], and azithromycin [ 170 ] have been used to treat the disease; however, they have had conflicting results and require further study [ 83 ] ( Table 3 ).…”
Section: Diagnosis and Treatment Key Pointsmentioning
confidence: 99%
“…Unike Tocilizumab and Sarilumab, the IL-6 target drug Siltuximab have affinity with IL-6. Though the efficacy of Siltuximab has been reported to be identical to Tocilizumab, it has produced a delayed normalization of IL-6 levels compared to the latter (Palanques-Pastor et al, 2020).…”
Section: Discussionmentioning
confidence: 99%